2017
DOI: 10.1108/md-02-2017-0113
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and propitiousness in strategic decision making

Abstract: Purpose The purpose of this paper is to examine the association between positive perceptions of politics (i.e. positive politics) and decision creativity and propitiousness (i.e. reaching unforeseen advantages while limiting unexpected problems). In addition, drawing from threat-rigidity effect theory the authors argue that such relationships will be resilient to external environmental threats and specifically macro-economic uncertainty. Design/methodology/approach The database for the analyses consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Our findings revealed that TMT procedural rationality and constructive political behavior have a significant impact on the performance of strategic decision-making. This indicates that both TMT procedural rationality and constructive political behavior are valuable resources for successful quality and satisfaction of strategic decisions [18,29,30,44]. Thus, this finding accords with previous scholarship that documents that TMTs' procedural rationality and constructive political behavior jointly enhance decision ability in exploring the complex environments to land on a successful quality and satisfaction of strategic decisions [1,3,26].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our findings revealed that TMT procedural rationality and constructive political behavior have a significant impact on the performance of strategic decision-making. This indicates that both TMT procedural rationality and constructive political behavior are valuable resources for successful quality and satisfaction of strategic decisions [18,29,30,44]. Thus, this finding accords with previous scholarship that documents that TMTs' procedural rationality and constructive political behavior jointly enhance decision ability in exploring the complex environments to land on a successful quality and satisfaction of strategic decisions [1,3,26].…”
Section: Discussionsupporting
confidence: 87%
“…Recent empirical studies have shown that procedural rationality and constructive political behavior is associated with higher quality strategic decisions [18,30,44]. We found that TMT behavioral integration is positively associated with TMT decision making performance.…”
Section: Theoretical Implicationsmentioning
confidence: 54%
See 2 more Smart Citations
“…To deepen the diverse perspectives, there has been recourse to combining diverse fields such as the rational, intuitive and political decision process as an option to generate the integrative approach for the various domains of SD. Following previous seminal literature (Dean & Sharfman, 1996;Elbanna, 2006Elbanna, , 2018Elbanna, Kapoutsis, & Mellahi, 2017), this study also applies the integrative perspective for addressing the coexistence of the synoptic and incremental perspective on the SD making process. To determine the scope and validity of the bibliometric analysis conducted, this study also applies the inclusion and exclusion criteria.…”
Section: Strategic Decision: Conceptual Backgroundmentioning
confidence: 99%